PERAN MODAL SENDIRI DAN MODAL PINJAMAN PADA PEROLEHAN SISA HASIL USAHA - Fandil Famdil; Zumrotun Nafi`ah; Herlina Wati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract The remaining operating results and special reserves are the determinants for calculating the turnover of capital, both own capital and loan capital. The purpose of this study was to determine whether the remaining amount of operating income would be influenced by own capital and loan capital in the KPRI